Ocular traumatic behavior in patients discharged from the Cuban Institute of Ophthalmology. - Dany Curbelo Concepción; Idalia Triana Casado; Juan C. Medina Perdomo (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
Background: Ocular traumas are regarded as an important cause of ophthalmologic morbidity and, at the same time, an important cause of the remaining injuries, most of the time handicapping those patients who suffer from them. Objective: to describe the behavior of the ocular traumas in patients who have been discharged from the Cuban Ophthalmology Institute "Ramón Pando Ferrer" in the period between January 2006 and December 2007. Methods: An observational-descriptive, transversal crossed study was implemented to 77 patients who were charged in under the diagnosis of ocular trauma. The analyzed variables included: age, sex, affected eye and location of the trauma, type of injury, place, circumstances and remaining injuries. Information was obtained out of clinical records, patient charts and by questioning the patients and was processed by using methods of descriptive statistics. Results: The anterior segment was the most affected (74.03%). The damaged iris 28.57 % and the cornea penetrating wound 18.18% were the most frequent injuries that caused the patients´ charging in. More than the half of the total of the cases were produced at home 54.55%, generally, during a sport practice or having amusing games. Conclusions: The final results show the occurrence of ocular traumas during certain events or factors. In order to prevent those traumas some actions could be carried out, above all, in early ages where the sight loss is quite painful.